2017
DOI: 10.1159/000472157
|View full text |Cite
|
Sign up to set email alerts
|

Components in Plasma-Derived Factor VIII, But Not in Recombinant Factor VIII Downregulate Anti-Inflammatory Surface Marker CD163 in Human Macrophages through Release of CXCL4 (Platelet Factor 4)

Abstract: Background: Hemarthrosis, or bleeding into the joints, is a hallmark of hemophilia. Heme triggers oxidative stress, inflammation, and destruction of cartilage and bone. The haptoglobin-CD163-heme oxygenase-1 (HO-1) pathway circumvents heme toxicity through enzymatic degradation of heme and transcription of antioxidant genes. Plasma-derived factor concentrates contain many proteins that might impact on cellular pathways in joints, blood, and vessels. Methods: Activation of platelets from healthy volunteers was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…6 Moreover, it has been shown that the joint and bone destruction in hemarthrosis, a typical hallmark of Hemophilia A, is caused by the inability of macrophages to adequately eliminate the oxidative stress created by the proteins (but not recombinant products) in the plasma-derived Factor VIII concentrates. 7 However, the exact cellular mechanisms by which oxidative stress contributes to Hemophilia A pathogenesis has not yet been clarified. 8 Dynamic thiol-disulfide exchange has become a common indicator in recent studies focusing on the role of oxidant stress in the pathophysiology of many diseases.…”
mentioning
confidence: 99%
“…6 Moreover, it has been shown that the joint and bone destruction in hemarthrosis, a typical hallmark of Hemophilia A, is caused by the inability of macrophages to adequately eliminate the oxidative stress created by the proteins (but not recombinant products) in the plasma-derived Factor VIII concentrates. 7 However, the exact cellular mechanisms by which oxidative stress contributes to Hemophilia A pathogenesis has not yet been clarified. 8 Dynamic thiol-disulfide exchange has become a common indicator in recent studies focusing on the role of oxidant stress in the pathophysiology of many diseases.…”
mentioning
confidence: 99%
“…Fresh frozen plasma (FFP) is the best and most accessible resource of FVIII. The temperature susceptibility of FVIII storage could restrict getting access to the high amount of FFP resource in a difficult situation (19)(20)(21)(22). Therefore, improving the half-life of the FVIII factor, while trying to maintain its activity and efficacy has a crucial impact on life-threatening disorders such as hemophilia (23).…”
mentioning
confidence: 99%